Belida Fish Cultivation (Notopterus notopterus, Pallas 1769) as Swamp Fish which is Nursed with Different Stocking densities - Sukendi Sukendi; Thamrin Thamrin; Ridwan Manda Putra; Ade Yulindra (ECOTONE, 2020)
Belida fish (Notopterus notopterus, Pallas 1769) is one of Indonesia's endemic fish which is often found in swamp waters having high economic value. The population of belida fish until now has decreased due to the high fishing activities in nature. To maintain the population of belida fish in order to remain sustainable from nature  is by cultivation activities. One of  important aspect in belida fish culture is the determination of stocking density used. This study aims to determine the optimum stocking densities in the belida fish farming activities. This research was conducted from June to August 2019 in the fish pond of Sungai Paku Village, Kampar Kiri Subdistrict, Riau. The design used was a completely randomized design with 3 levels of treatment and 3 replications. The treatment used in this study was stocking density consisting of 5, 10 and 15 fish / m3. The results showed that the 5 fish / m3 stocking density treatment produced the optimum fish growth with absolute length growth value (11.48 cm), absolute weight growth (48.73 g), daily growth rate (2.83%), survival rate (86 , 7%), fat retention 1.27% and protein retention value 19.83%.